Cover the Antique. The case of the Arena of Verona - Giuseppe Fallacara; Ubaldo Occhinegro; Micaela Pignatelli (Agathón)
The International Competition for Verona Arena Coverage has animated the international debate on the theme of contemporary intervention on ancient architecture. The NFRG of Politecnico of Bari has proposed an experimental, reversible, modular and structurally independent roofing solution. Starting from the study of the velaria, the group has come to a design research inspired by the Kinetic Architecture.